Use of Anatomage tables in a large first year core unit - Fyfe, Georgina; Fyfe, Susan; Dye, Danielle; Radley-Crabb, Hannah (Electric Dreams Proceedings ascilite 2013, 2013)
Anatomage tables were incorporated into a large core unit in health sciences at Curtin University to replace cadaver material. Students worked in groups of eight around the table, as one of several stations in weekly workshops facilitated by tutors. Tutors and students completed a survey asking about their use of technology and their experiences with the Anatomage tables. Tutors also contributed to focus groups (n=16), and student interaction around the table was recorded on camera. Student survey response was 18% (n= 326) and for tutors, 69% (n=22). Preliminary analysis suggests that most students found the Anatomage tables good for ideas of scale and relationships of organ structures, and liked being able to rotate the images, but were less impressed with graphics quality and the limitations to group interaction. Tutors felt well-prepared for using the tables but were frustrated by technical issues, and few thought the tables were a good investment.